MicroRNA profiling of diagnostic needle aspirates from patients with pancreatic cancer - Ali, S; Saleh, H; Sethi, S; Sarkar, F H; Philip, P A (British journal of cancer, 2012)
Background: A major challenge to the development of biomarkers for pancreatic cancer (PC) is the small amount of tissue obtained at the time of diagnosis. Single-gene analyses may not reliably predict biology of PC because of its complex molecular makeup. MicroRNA (miRNA) profiling may provide a more informative molecular interrogation of tumours. The primary objective of this study was to determine the feasibility of performing miRNA arrays and quantitative real-time PCR (qRT–PCR) from archival formalin-fixed paraffin-embedded (FFPE) cell blocks obtained from fine-needle aspirates (FNAs) that is the commonest diagnostic procedure for suspected PC. Methods: MicroRNA expression profiling was performed on FFPE from FNA of suspicious pancreatic masses. Subjects included those who had a pathological diagnosis of pancreatic adenocarcinoma and others with a non-malignant pancreatic histology. Exiqon assay was used to quantify miRNA levels and qRT–PCR was used to validate abnormal expression of selected miRNAs. Results: A total of 29 and 15 subjects had pancreatic adenocarcinoma and no evidence of cancer, respectively. The RNA yields per patient varied from 25 to 100 ng. Profiling demonstrated deregulation of over 228 miRNAs in pancreatic adenocarcinoma of which the top 7 were further validated by qRT–PCR. The expression of let-7c, let-7 f, and miR-200c were significantly reduced in most patients whereas the expression of miR-486-5p and miR-451 were significantly elevated in all pancreas cancer patients. MicroRNAs let-7d and miR-423-5p was either downregulated or upregulated with a significant inter-individual variation in their expression. Conclusion: This study demonstrated the feasibility of using archival FFPE cell blocks from FNAs to establish RNA-based molecular signatures unique to pancreatic adenocarcinoma with potential applications in clinical trials for risk stratification, patient selection, and target validation.